2019
DOI: 10.1161/circulationaha.118.036053
|View full text |Cite
|
Sign up to set email alerts
|

C-X-C Motif Chemokine Receptor 4 Blockade Promotes Tissue Repair After Myocardial Infarction by Enhancing Regulatory T Cell Mobilization and Immune-Regulatory Function

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 51 publications
6
72
1
Order By: Relevance
“…We used Real-Time PCR to quantify the mRNA levels of CXCR4 and its ligand, the stromal cell-derived factor 1 (SDF-1), also known as CXCL12. The CXCR4 mRNA levels significantly increased after 7 days ( Figure 6A) and 60 days ( Figure 6B) of MI induction, corroborating previous reports [53,54]. Treatment with HPβCD/Ang-(1-7) reduced the CXCR4 mRNA to its basal levels (similar to Sham) after 7 days ( Figure 6A) and 60 days ( Figure 6B).…”
Section: Validation Of Cxcr4 As a Downstream Effector Of Hpβcd/ang-(1supporting
confidence: 89%
See 1 more Smart Citation
“…We used Real-Time PCR to quantify the mRNA levels of CXCR4 and its ligand, the stromal cell-derived factor 1 (SDF-1), also known as CXCL12. The CXCR4 mRNA levels significantly increased after 7 days ( Figure 6A) and 60 days ( Figure 6B) of MI induction, corroborating previous reports [53,54]. Treatment with HPβCD/Ang-(1-7) reduced the CXCR4 mRNA to its basal levels (similar to Sham) after 7 days ( Figure 6A) and 60 days ( Figure 6B).…”
Section: Validation Of Cxcr4 As a Downstream Effector Of Hpβcd/ang-(1supporting
confidence: 89%
“…This event is independent of CXCL12 regulation. Our data confirm CXCR4 as a potential MI biomarker and therapeutic target [51,52,54,68]..…”
Section: Validation Of Cxcr4 As a Downstream Effector Of Hpβcd/ang-(1supporting
confidence: 81%
“…It might therefore be safe to conclude that the PET/CT approach used in this study could offer a suitable method for monitoring local adaptive immune responses in MI patients. Indeed, a recently published study revealed that CXCR4 plays an important role in controlling T cell trafficking in the context of EMI and thereby influences the healing outcome (65), and these findings provide great mechanistic support for our clinical findings.…”
Section: Methodssupporting
confidence: 82%
“…C‐X‐C motif chemokine receptor (CXCR) family is a member of seven‐transmembrane receptors, which exerts chemoattractant effects on leucocytes and other cell types in controlling cell activation and guiding cell movements under basal and inflammatory conditions . There are 8 members of C‐X‐C motif chemokine receptors (CXCR1‐8), which play the critical roles in immune, neurodegenerative and cardiovascular diseases . Recent reports show that several C‐X‐C motif chemokine receptors also play the fundamental roles in the progression of CKD, such as CXCR1, CXCR6 and particularly CXCR4 .…”
Section: Discussionmentioning
confidence: 99%